2016
DOI: 10.1371/journal.pone.0168024
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Faecal Carriage of ESBL-Producing Enterobacteriaceae among Children in Dar es Salaam, Tanzania

Abstract: BackgroundFaecal carriage of ESBL-producing bacteria is a potential risk for transmission and infection. Little is known about faecal carriage of antibiotic resistance in Tanzania. This study aimed to investigate the prevalence of faecal carriage of ESBL-producing Enterobacteriaceae and to identify risk factors for carriage among young children in Tanzania.Methodology/Principal FindingsFrom August 2010 to July 2011, children below 2 years of age were recruited in Dar es Salaam, including healthy community chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

28
106
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(147 citation statements)
references
References 30 publications
28
106
12
1
Order By: Relevance
“…Potential reasons for the observed difference include several factors such as; different ESBL detection techniques and specimen used, whereas in a study by Sabrina et al they used urine specimen and ESBL-E test strip for ESBL detection. Furthermore the carriage rate in our study is also higher compared to that reported among hospitalized children in Dar es Salaam, Tanzania (18). This difference may be accounted for by the difference in study population, whereby the study population in this study were children versus adults in our study.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…Potential reasons for the observed difference include several factors such as; different ESBL detection techniques and specimen used, whereas in a study by Sabrina et al they used urine specimen and ESBL-E test strip for ESBL detection. Furthermore the carriage rate in our study is also higher compared to that reported among hospitalized children in Dar es Salaam, Tanzania (18). This difference may be accounted for by the difference in study population, whereby the study population in this study were children versus adults in our study.…”
Section: Discussioncontrasting
confidence: 60%
“…However, in a study done among children by Tellevic and his colleagues, children hospitalized due to diarrhea had lower carriage rate compared to those hospitalized due to other diseases, probably because the latter group included children with many diverse conditions (18). The pattern observed in our study can be explained by the fact that diarrhea cause changes in the gut microbiota which provides conducive environment for exchange of resistance genes between inter and intra species including the indigenous organisms (23).…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…The overall prevalence of ESBL in the three interfaces was found to be 22.62% (95% CI: 21.08–24.16) (Blomberg et al., ; Moremi et al., ; Mshana, Imirzalioglu, et al., ; Mshana et al., , ; Ndugulile, Jureen, Harthug, Urassa, & Langeland, ; Onken, Said, Jorstad, Jenum, & Blomberg, ; Seni et al., ; Tellevik et al., ). The lowest and highest ESBL prevalence were 0.90% (95% CI: 0.46–1.34) and 53.40% (95% CI: 41.96–64.84), respectively (Blomberg et al., ; Moremi et al., ) (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…With regard to ESBL‐PE species, E. coli and Klebsiella species were the predominant bacterial species (93.2%) compared to other bacterial species, which accounted for only 6.8% (Blomberg et al., ; Moremi et al., ; Mshana et al., , ; Mshana, Imirzalioglu, et al., ; Ndugulile et al., ; Onken et al., ; Seni et al., ; Tellevik et al., ) (Figure ).…”
Section: Resultsmentioning
confidence: 99%